Recommendations for Prosecution Policies Concerning Offenders with Mental Disabilities in Indonesia from a Victimological Perspective - Amir Amir; Annisa Putri Amalia; budiarsih budiarsih (Dinasti Research, 2026)
The development of criminal law in Indonesia reflects a shift from a retributive approach toward a more humane and restorative justice-oriented approach, including in the treatment of offenders with mental disabilities. This study aims to analyze the forms of legal protection afforded to offenders with mental disabilities from a victimological perspective and to formulate more responsive prosecution policy recommendations. The research employed an empirical legal method with a qualitative approach through interviews, observations, and document analysis involving police investigators, public prosecutors, forensic psychiatrists, academics, and disability advocacy institutions. The findings indicate that legal protection has been provided through the postponement of legal status determination pending psychiatric assessment, the use of forensic psychiatric examinations, the provision of reasonable accommodation, and the prioritization of rehabilitative measures over imprisonment. However, its implementation remains suboptimal due to the absence of standardized technical guidelines, limited mental health facilities, and the persistence of punitive orientations within the criminal justice system. From a victimological perspective, offenders with mental disabilities occupy a dual position as both offenders and victims who are vulnerable to secondary victimization. Therefore, prosecution policies should emphasize rehabilitative and therapeutic approaches, as well as the protection of the rights of persons with disabilities, in order to achieve substantive justice within Indonesia’s criminal justice system.